Trimethylamine N-Oxide levels increase in patients with severe and non-severe COVID-19 - Yasak, Ibrahim Halil; Yilmaz, Mustafa; Ceylan, Mehmet Resat; Koyuncu, Ismail; Seyhanli, Eyyup Sabri (Bayrakol Medical Publisher, 2023)
Aim: This study aimed to measure and evaluate serum trimethylamine N-oxide (TMAO) levels in patients with COVID-19. Material and Methods: The patients were divided into three groups according to their polymerase chain reaction (PCR) results and the clinical picture of the disease: Group 1 (negative PCR result, n = 44), Group 2 (positive PCR result and non-severe disease, n = 38) and Group 3 (positive PCR result and severe disease, n = 45).Results: TMAO levels were significantly different among the three patient groups. Post Hoc Dunn's analysis revealed a significant difference between Group 1 and Group 2 (p = 0.006), Group 1 and Group 3 (p < 0.001) and Group 2 and Group 3 (p = 0.031). ROC analysis revealed that a cut-off value of 2.92 had a sensitivity of 74.70%, a specificity of 68.18%, a positive predictive value of 81.6% and a negative predictive value of 58.8%.Discussion: The results of this study demonstrated that TMAO levels increased in the patients with COVID-19, and further TMAO levels increased as the severity of the disease progressed.
Keywords: Biomarkers; COVID-19; Peripheral Blood; Severe; Trimethylamine N-oxide